Engineering Novel Lab Devices Using 3D Printing and Microcontrollers. (October 2018) - Courtemanche, Jean; King, Samson; Bouck, David
The application of 3D printing and microcontrollers allows users to rapidly engineer novel hardware solutions useful in a laboratory environment. 3D printing is transformative as it enables the rapid fabrication of adapters, housings, jigs, and small structural elements. Microcontrollers allow for the creation of simple, inexpensive machines that receive input from one or more sensors to trigger a mechanical or electrical output. Bringing these technologies together, we have developed custom solutions that improve capabilities and reduce costs, errors, and human intervention. In this article, we describe three devices: JetLid, TipWaster, and Remote Monitoring Device (REMIND). JetLid employs a microcontroller and presence sensor to trigger a high-speed fan that reliably de-lids microtiter plates on a high-throughput screening system. TipWaster uses a presence sensor to activate an active tip waste chute when tips are ejected from a pipetting head. REMIND is a wireless, networked lab monitoring device. In its current implementation, it monitors the liquid level of waste collection vessels or bulk liquid reagent containers. The modularity of this device makes adaptation to other sensors (temperature, humidity, light/darkness, movement, etc.) relatively simple. These three devices illustrate how 3D printing and microcontrollers have enabled the process of rapidly turning ideas into useful devices.